Acute Paraparesis after Epidural Corticosteroid Injection Revealing Spinal Dural Arteriovenous Fistula in a HIV Patient - Anouk Le Goueff; Nicolas Mavroudakis; Benjamin Mine; Olivier De Witte; Gauthier Remiche (European Journal of Case Reports in Internal Medicine, 2020)
Spinal dural arteriovenous fistulas (SDAVFs) are often misdiagnosed as their symptoms are non-specific, leading to treatment delay and a poor outcome. We describe the case of a 53-year-old man with a history of progressive paraparesis that worsened abruptly after an epidural corticosteroid injection. We highlight here the need for high diagnostic suspicion for an SDAVF in patients deteriorating after an epidural injection and an indication of repeated spine imaging in such cases. Finally, this is the first reported case of an SDAVF in a HIV-positive patient and it emphasizes the need for a broad differential diagnosis.